Property rights beyond property limits: an analysis of the right to unobstructed view in Kenya. - Takah, Valerie Mitchelle (Strathmore University, 2018)
Land use planning regulations in developing countries often fail to achieve greater efficiency and equity in the use of urban land. As a result, plans often bear little or no relation to the people's needs and wishes and they are in any case distorted by limited implementation and their rigid nature. These problems are exacerbated, particularly in the face of rapid change, by lack of consistent overall policy framework and failure to involve the public in the formulation of laws and regulations which affect their interests. This study seeks to evaluate whether Kenyan Law is capable of securing the right to an unobstructed view from property in Kenya. The Study analyses the Land use planning system in the United Kingdom with particular focus on London which has protected views in order to reserve its identity. It can be concluded that, the Kenyan Land use planning system has not yet adopted the bottom up approach in the formulation of regulations. Hence, interests such as, an unobstructed view can not be protected.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Property rights; Unobstructed view; Urban land; Land planning system